1999
DOI: 10.1002/(sici)1097-0142(19990115)85:2<257::aid-cncr1>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Actions of heparin that may affect the malignant process

Abstract: BACKGROUND Heparin has many actions that may affect the malignant process, especially metastasis. METHODS The author conducted an extensive review of the available medical literature about heparin activity that may apply to important factors involved in the malignant process. RESULTS Thrombin is generated by tumors, and the resultant fibrin formation impedes natural killer cell activity. Microthrombi arrest tumor cells in capillaries. Heparin prevents the formation of thrombin and neutralizes its activity. Ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
80
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 188 publications
0
80
0
1
Order By: Relevance
“…[9][10][11][12]. A few clinical trials also suggested a beneficial effect of heparin in humans with cancer (13)(14)(15)(16)(17).…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…[9][10][11][12]. A few clinical trials also suggested a beneficial effect of heparin in humans with cancer (13)(14)(15)(16)(17).…”
Section: Biochemistry For the Article ''Functional Transitions In Mymentioning
confidence: 99%
“…As a result, modified heparin derivatives which have low anticoagulant activities and still preserve anti-adhesion biological activities were developed. 37,38 Here we tested the effects of heparin and modified heparins with lower anticoagulant activities in inhibiting the interaction of melanoma cells with platelets mediated by a IIb b 3 . In the eight modified heparins, RO-heparin, CR-heparin, 2,3-O-desulfate heparin and N-2,3-desulfate heparin exhibited excellent ability in inhibiting the stable attachment of A375 cells to GP-CHO cells or platelets.…”
Section: Discussionmentioning
confidence: 99%
“…21 Kakkar and Williamson 22,23 and Engelberg 24 noted the antimetastatic effect of heparin and fractionated heparin, and randomized prospective studies currently are in progress. More specifically, in vitro and in vivo murine models have shown that platelet aggregation is one of the mechanisms that promotes metastatic growth by protecting the metastatic tumor cells from natural killer cell cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%